1999
DOI: 10.1038/7280
|View full text |Cite
|
Sign up to set email alerts
|

A physiological correlate of the 'spotlight' of visual attention

Abstract: Here we identify a neural correlate of the ability to precisely direct visual attention to locations other than the center of gaze. Human subjects performed a task requiring shifts of visual attention (but not of gaze) from one location to the next within a dense array of targets and distracters while functional MRI was used to map corresponding displacements of neural activation within visual cortex. The cortical topography of the purely attention-driven activity precisely matched the topography of activity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
413
3
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 665 publications
(462 citation statements)
references
References 30 publications
43
413
3
3
Order By: Relevance
“…Heinze and colleagues (Heinze et al, 1994) demonstrated with positron emission tomography (PET) that spatial attention leads to stronger activations in extrastriate cortex in the hemisphere contralateral to the attended side of a stimulus array spanning both hemifields. With the advent of fMRI and its greater spatial resolution, it has been shown that spatial attention exhibits fine retinotopy Brefczynski and DeYoe, 1999). In fact, the cortical topography of purely attention-driven activity precisely matches the topography of activity evoked by visual targets as revealed by retinotopic mapping.…”
Section: The Effect Of Attention On Sensory Processingmentioning
confidence: 89%
“…Heinze and colleagues (Heinze et al, 1994) demonstrated with positron emission tomography (PET) that spatial attention leads to stronger activations in extrastriate cortex in the hemisphere contralateral to the attended side of a stimulus array spanning both hemifields. With the advent of fMRI and its greater spatial resolution, it has been shown that spatial attention exhibits fine retinotopy Brefczynski and DeYoe, 1999). In fact, the cortical topography of purely attention-driven activity precisely matches the topography of activity evoked by visual targets as revealed by retinotopic mapping.…”
Section: The Effect Of Attention On Sensory Processingmentioning
confidence: 89%
“…Extensive activations also involved the medial occipital lobes (cuneus and lingual gyrus) bilaterally, extending anteriorly into the precuneus and posterior parahippocampal gyrus. These medial occipital activations, which likely reflect shifts of attention from foveal to peripheral visual locations (Brefczynski & DeYoe, 1999;Kastner et al, 1999;Tootell et al, 1998), are not relevant to the aims of this study and will not be discussed further. Additional activations involved the left frontoparietal operculum and supramarginal gyrus, right dorsal prefrontal cortex (MFG and superior frontal sulcus), bilateral suborbital sulcus and gyrus rectus, left orbitofrontal cortex (OFC), left mid-cingulate gyrus, and right angular gyrus.…”
Section: Fmrimentioning
confidence: 99%
“…For one, attending a location boosts the neural activity to elements presented at that location (Brefczynski & DeYoe, 1999;Datta & DeYoe, 2009;Gandhi, Heeger, & Boynton, 1999;Somers, Dale, Seiffert, & Tootell, 1999). It has further been suggested that attending both rival images leads to a boost in the neural response, which increases the effective contrast of rivaling images (Paffen et al, 2006).…”
mentioning
confidence: 99%